1995
DOI: 10.1016/0735-1097(94)00543-y
|View full text |Cite
|
Sign up to set email alerts
|

Time course of improvement in left ventricular function, mass and geometry in patients with congestive heart failure treated with beta-adrenergic blockade

Abstract: Patients with heart failure treated with metoprolol do not demonstrate an improvement in systolic performance until after 1 month of therapy and may have a mild reduction in function initially. Long-term therapy with metoprolol results in a reversal of maladaptive remodeling with reduction in left ventricular volumes, regression of left ventricular mass and improved ventricular geometry by 18 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

19
266
1
12

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 487 publications
(298 citation statements)
references
References 42 publications
19
266
1
12
Order By: Relevance
“…␤-Blockade improves LVEF by biologically augmenting myocyte and chamber contractility. [1][2][3][4] This improvement does not occur immediately but rather between 1 and 3 months of therapy. 3 A partial explanation of biological improvement in LVEF may be upregulation of sarcoplasmic reticulum calcium ATPase (SERCA2), a protein that controls calcium sequestration, and an increase in the relative amount of ␣-myosin heavy chain.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…␤-Blockade improves LVEF by biologically augmenting myocyte and chamber contractility. [1][2][3][4] This improvement does not occur immediately but rather between 1 and 3 months of therapy. 3 A partial explanation of biological improvement in LVEF may be upregulation of sarcoplasmic reticulum calcium ATPase (SERCA2), a protein that controls calcium sequestration, and an increase in the relative amount of ␣-myosin heavy chain.…”
Section: Discussionmentioning
confidence: 98%
“…[1][2][3][4] This improvement does not occur immediately but rather between 1 and 3 months of therapy. 3 A partial explanation of biological improvement in LVEF may be upregulation of sarcoplasmic reticulum calcium ATPase (SERCA2), a protein that controls calcium sequestration, and an increase in the relative amount of ␣-myosin heavy chain. 16 In the absence of contractile reserve (ie, when myocytes have been supplanted by replacement fibrosis because of cell death and interstitial remodeling 1,17 ), ventricular function cannot improve by this biological mechanism because there are not enough contractile units.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In CHF, drugs classified as ␤-blockers (␤-AR antagonists and inverse agonists) were once contraindicated because acute administration decreased cardiac output and produced other negative inotropic effects (8). However, large clinical trials have shown that chronic administration of certain ␤-blockers improves cardiac output and decreases mortality (9,10). Presently, ␤-blockers are contraindicated in asthma because their acute administration may cause airway narrowing (11,12).…”
mentioning
confidence: 99%